Posisi Semi Fowler 30o Meningkatkan Nilai Saturasi Oksigen pada Pasien Stroke Non Hemoragik - Yuliastuti, Fitri; Faridah, Umi; Jauhar, Muhamad; Kanan, Thanalechumy (Journal of Pubnursing Sciences, 2025)
Background: Stroke is a disruption of blood and oxygen flow to the brain that represents a major global and national health problem, causing hypoxia and cerebral injury due to obstruction or rupture of cerebral blood vessels, with risk factors including hypertension, lifestyle, and diet. Prompt management is essential, one of which is the 30° semi-Fowler position, which is believed to improve oxygenation.  Aims: aimed to analyze the effect of the 30° semi-Fowler position on increasing oxygen saturation in non-hemorrhagic stroke patients at Dr. Rehatta Regional Hospital, Central Java Province.  Method: The research design was a quasi-experiment without a control group, conducted in June–July 2025 with a total of 20 respondents using a total sampling technique. Inclusion criteria were patients diagnosed with stroke by a physician, level of consciousness 12–15, and hospitalized, while exclusion criteria were patients with mechanical ventilators. The research instrument was a Nihon Kohden oximeter, type 68042-17 BSM, calibrated in advance. The intervention consisted of the 30° semi-Fowler position for 30 minutes, carried out twice daily for two days (a total of four sessions). Oxygen saturation (SpO₂) was measured at minutes 0, 15, and 30, along with vital signs monitoring. Data analysis using the Wilcoxon Test showed a significant difference in SpO₂ values before and after the intervention (p<0.000; p<0.05).  Result: The results demonstrated that the 30° semi-Fowler position effectively increases oxygen saturation in non-hemorrhagic stroke patients.  The implication of this study is the need for hospitals to develop standard operating procedures (SOPs) for the application of the 30° semi-Fowler position in non-hemorrhagic stroke patients, especially in Intensive Care Units, as an evidence-based independent nursing intervention to improve the quality of care and patient safety.